High dependency of underprivileged Muslim on Zakat assistance in the state of Selangor - Abdul Basith Hamid; Raemah Abdullah Hashim (2019)
This paper aims to explore the high dependency of underprivileged Muslims on zakat assistance in the state of Selangor. By the end of the year 2019, Selangor is one of the most prosperous states in Malaysia, distribution of zakat assistance is expected to reach to more than 50,000 families in the category of poor and needy 'asnaf fakir and miskin'. Over one billion Ringgit Malaysia is being allocated by the state zakat corporation. However, over the years the trend of number recipients of zakat is ever increasing. This paper also looks into issues related to the management of collection and distribution of zakat and also the reasons behind the increasing trend. Knowledge of underprivileged Muslim is of concern especially on the ability to raise themselves above poverty and not continuously seeking alms from zakat. Their religious belief takes an unprecedented stand that their dependence as their birth right as Muslim. On top of these issues, a situational factor which is deemed important is also being investigated. Twenty-five (25) respondents were interviewed among the 'asnaf fakir and miskin'. The finding indicated that the most important reason for the increasing number of underprivileged Muslim in Selangor is due to the situational factor. The increase in the cost of living standard is also the reason for the increase of alms seekers from zakat. From this study, it was found the Lembaga Zakat Selangor as the sole body in managing zakat collection and distribution have carried out their duty in a responsible manner but can further elevate their management effectiveness to a more highly systematic manner to be one of the best zakat managing body in the world. (Abstract by authors)